Evaluation of Stability and Accuracy Compared to the Westergren Method of ESR Samples Analyzed at VES-MATIC 5 - Maria Lorubbio; Daniela Diamanti; Alessandro Ghiandai; Carolina Pieroni; Donatella Bonini; Massimiliano Pettinari; Gabriele Gorini; Stefania Bassi; Paola Meloni; Agostino Ognibene (Diagnostics, 2024)
The Erythrocyte Sedimentation Rate (ESR) is a diagnostic estimator of systemic inflammation as a reflection of acute phase proteins circulating in the blood. The purpose of this manuscript is to evaluate the blood stability at room temperature (RT) and at 4 °C to avoid ESR diagnostic errors, as well as the accuracy of the VES-MATIC 5 analyzer. The ESR stability evaluation at RT for 24 h (4 h “T1”, 6 h “T2”, 8 h “T3”, 10 h “T4”, 24 h “T5”) and at 4 °C (24 h, 36 h, 48 h) was carried out using 635 total samples, starting with T0 (2 h of venipuncture). For method comparison, 164 patients were analyzed using VES-MATIC 5 and then the Westergren reference method. The sample at RT is established by a significant gradual decrease in correlation R = 0.99 (T0 vs. T1), R = 0.97 (T0 vs. T2), R = 0.92 (T0 vs. T3), R = 0.87 (T0 vs. T4), and R = 0.40 (T0 vs. T5). The stability at 4 °C after 24 h, 36 h, and 48 h showed a regression of R = 0.99, R = 0.97, and R = 0.95, respectively. Therefore, ESR measurements on RT samples beyond 6 h after collection cannot be carried out, but the ESR can be measured until 36 h for samples stored at 4 °C. Moreover, the VES-MATIC 5 accuracy performance compared to the Westergren method (R = 0.96) is confirmed.